Hypogammaglobulinemia associated with accelerated catabolism of IgG secondary to its interaction with an IgG-reactive monoclonal IgM - Waldmann, Thomas A.; Johnson, John S.; Talal, Norman (The Journal of Clinical Investigation, 1971)
Hypogammaglobulinemia due to a new pathophysiological mechanism was studied in a patient with Sjögren's syndrome, a monoclonal IgM and a mixed (IgM-IgG) cryoglobulinemia. The IgM (IgMdk) component of the cryogel possessed light chains of λ-type with highly restricted electrophoretic mobility analagous to those of a Waldenström's macroglobulin. IgMdk reacted specifically with native IgG, with IgG subclasses 1, 2, and 4, and with the Fc piece of IgG to form a cryogel. Serum concentrations of IgG 1, 2, and 4 were 10% of normal, whereas the IgG3 level was slightly increased and the IgM level was markedly increased. Viscosity and analytical ultracentrifugation studies with the purified mixed cryogel (IgM-LgG) indicated soluble complex formation over a temperature range (36-38°C) attainable in vivo. Immunoglobulin turnover studies revealed a markedly elevated rate of IgM synthesis with a normal survival of IgM, IgA, and IgE. IgG3, which failed to form complexes with IgMdk at body temperature, had a normal synthetic rate and survival. In contrast, the other IgG subclasses showed reduced synthesis and shortened survival. These studies are the first indicating a short survival of some IgG subclasses with a normal survival of another. The hypogammaglobulinemia appears to be due in part to a new mechanism of accelerated protein catabolism: The rapid elimination of IgG due to its interaction with an IgG-reactive monoclonal IgM.